A Detailed Investigation of HD 209458 b HST and JWST Transmission Spectra with SANSAR - Avinash Verma; Jayesh Goyal; Swaroop Avarsekar; Gaurav Shukla (The Astronomical Journal)
HD 209458 b is the first exoplanet on which an atmosphere was detected. Since then, its atmosphere has been investigated using multiple telescopes and instruments. However, many of its atmospheric constraints remain debatable. While Hubble Space Telescope (HST) observations suggested a highly subsolar metallicity, recent JWST NIRCam observations by Q. Xue et al. constrained a supersolar metallicity with highly subsolar C/O. In this work, we show a detailed investigation of HD 209458 b transmission spectra observations from JWST and HST using SANSAR , a newly developed planetary atmosphere modeling framework, with free, equilibrium chemistry and self-consistent grid retrievals. The overall best-fitting model with free retrievals ( ${χ }_{{\rm{red}}}^{2}$ = 1.21) constrains its metallicity and C/O to be highly subsolar, while equilibrium chemistry and grid retrievals ( ${χ }_{{\rm{red}}}^{2}$ = 1.27 and 1.30, respectively) are consistent with solar values using Space Telescope Imaging Spectrograph (STIS)+WFC3+NIRCam observations. The retrieved abundances of H _2 O and CO _2 are almost 3 orders of magnitude lower (highly subsolar) with STIS+WFC3+NIRCam compared to just NIRCam, using free retrievals. NIRCam observations alone also result in misleading constraints on metallicity and C/O, with equilibrium chemistry and grid retrieval. We find that the model choice of varying C/H or O/H to vary the C/O in equilibrium chemistry retrievals leads to different metallicity constraints with NIRCam, but similar constraints with STIS+WFC3+NIRCam. We conclude that NIRCam observations alone can lead to overestimation of abundances for exoplanet atmospheres and, therefore, should be used in combination with UV/optical and near-infrared observations to obtain robust constraints on abundances, C/O, and metallicity. In particular, even though we can detect the CO _2 feature with just NIRCam, we cannot constrain its abundances robustly without the optical baseline.